2016
DOI: 10.1073/pnas.1617415113
|View full text |Cite
|
Sign up to set email alerts
|

Quorum sensing controls the Pseudomonas aeruginosa CRISPR-Cas adaptive immune system

Abstract: CRISPR-Cas are prokaryotic adaptive immune systems that provide protection against bacteriophage (phage) and other parasites. Little is known about how CRISPR-Cas systems are regulated, preventing prediction of phage dynamics in nature and manipulation of phage resistance in clinical settings. Here, we show that the bacterium Pseudomonas aeruginosa PA14 uses the cell-cell communication process, called quorum sensing, to activate cas gene expression, to increase CRISPR-Cas targeting of foreign DNA, and to promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
223
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 265 publications
(247 citation statements)
references
References 49 publications
11
223
1
1
Order By: Relevance
“…The absence of this mechanism is possibly because this strategy would be unable to interfere with CRISPR nucleases that were assembled prior to infection. Nonetheless, many CRISPR systems are tightly regulated and are often activated in response to cell density and other factors (Høyland-Kroghsbo et al, 2016; Patterson et al, 2016, 2017). Inhibition of crRNA binding could be an effective Acr method to inhibit those systems where RNP assembly coincides with phage infection, and such inhibitors may yet be discovered.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of this mechanism is possibly because this strategy would be unable to interfere with CRISPR nucleases that were assembled prior to infection. Nonetheless, many CRISPR systems are tightly regulated and are often activated in response to cell density and other factors (Høyland-Kroghsbo et al, 2016; Patterson et al, 2016, 2017). Inhibition of crRNA binding could be an effective Acr method to inhibit those systems where RNP assembly coincides with phage infection, and such inhibitors may yet be discovered.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that quorum sensing has a role in controlling the Pseudomonas aeruginosa CRISPR-Cas adaptive immune system (Høyland-Kroghsbo et al, 2016) and the TCS BfiSR affects the production of proteins involved in virulence, post-translational modification, and quorum sensing (Petrova and Sauer, 2010). We therefore reasoned that TCS might also affect the CRISPR-Cas immune system of R. anatipestifer .…”
Section: Discussionmentioning
confidence: 99%
“…We know that each living cell possesses quite an impressive intelligence [13,28,31]. Cell colony's intelligence as any other group of living creatures grows with a number of cells (creatures) exponentially [32,33]. Each level of quantity generally requires a new degree of hierarchical organization and at a certain level, it obtains new quality.…”
Section: Critical Massmentioning
confidence: 99%